2022
DOI: 10.1016/j.jceh.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Liver Biopsy in Patients With Alcohol-Associated Liver Disease With Acute-on-Chronic Liver Failure

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…This may be relevant when trying to differentiate biliary obstruction from hepatic dysfunction. However, liver biopsy is less effective for predicting mortality than non-invasive scoring systems such as MELD and Maddrey’s Discriminant Function (DF) [ 39 ]. Several prognostic scoring systems have been validated for use in AH.…”
Section: Acute Liver Diseasesmentioning
confidence: 99%
“…This may be relevant when trying to differentiate biliary obstruction from hepatic dysfunction. However, liver biopsy is less effective for predicting mortality than non-invasive scoring systems such as MELD and Maddrey’s Discriminant Function (DF) [ 39 ]. Several prognostic scoring systems have been validated for use in AH.…”
Section: Acute Liver Diseasesmentioning
confidence: 99%
“…Some studies have claimed that patients with ACLF of alcoholic etiology have significantly prolonged hospital stay, severe COVID-19, admission to the intensive care unit and higher mortality[ 37 , 38 ], while others have shown that ACLF is often triggered not only by ongoing alcohol consumption, but also gastrointestinal bleeding and/or infections, and from a pathophysiological point of view it is characterized by uncontrolled systemic inflammation coupled with paradoxical immunoparesis. ACLF has a clear pathogenesis and epidemiological burden and is different from decompensated cirrhosis; it represents a challenging condition with a rapid clinical course, high short-term mortality and varying clinical phenotypes[ 39 , 40 ].…”
Section: Sars-cov-2 Effects On the Livermentioning
confidence: 99%